Substantive law in investment treaty arbitration - Sasson, Monique (International Arbitration Law Library Series ;, 2017)
Substantive Law in Investment Treaty Arbitration' is a clear analysis of previously unexplored aspects of investment arbitration. This second edition of what has rapidly become the pre-eminent work on the role of municipal law in investment treaty arbitration is justified not only by the accelerating appearance of investment treaty awards, but also by the continuing, serious problems in the application of international law by investment treaty arbitral tribunals. The book considers key matters of substantive law in which a renvoi to municipal law must be conducted if an investment treaty tribunal is to reach sound results under international law.